2020
DOI: 10.3389/fcell.2020.564581
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 1 Is Essential for Muscle Regeneration and Overload Muscle Fiber Hypertrophy

Abstract: Satellite cell proliferation is an essential step in proper skeletal muscle development and muscle regeneration. However, the mechanisms regulating satellite cell proliferation are relatively unknown compared to the knowledge associated with the differentiation of satellite cells. Moreover, it is still unclear whether overload muscle fiber hypertrophy is dependent on satellite cell proliferation. In general, cell proliferation is regulated by the activity of cell cycle regulators, such as cyclins and cyclin-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In recent years, alternative models for preventing satellite cell fusion in vivo have emerged. These models disrupt some aspect of satellite cell function via genetic means, 60 , 88 , 184 , 185 , 186 , 187 and have generally concluded that satellite cell‐mediated myonuclear accretion is required for overload‐induced hypertrophy. Given dissonance between results from the Pax7‐DTA mouse versus other models, we speculate that the presence of dysfunctional satellite cells could be more deleterious to load‐induced muscle adaptation than removing satellite cells from the muscle environment altogether; however, the muscle being overloaded (e.g., extensor digitorum longus versus plantaris), post‐surgery/stimulus recovery status, genetic background of the mice, diet, or a variety of other factors may also in part explain the discrepancy.…”
Section: Recent Resultsmentioning
confidence: 99%
“…In recent years, alternative models for preventing satellite cell fusion in vivo have emerged. These models disrupt some aspect of satellite cell function via genetic means, 60 , 88 , 184 , 185 , 186 , 187 and have generally concluded that satellite cell‐mediated myonuclear accretion is required for overload‐induced hypertrophy. Given dissonance between results from the Pax7‐DTA mouse versus other models, we speculate that the presence of dysfunctional satellite cells could be more deleterious to load‐induced muscle adaptation than removing satellite cells from the muscle environment altogether; however, the muscle being overloaded (e.g., extensor digitorum longus versus plantaris), post‐surgery/stimulus recovery status, genetic background of the mice, diet, or a variety of other factors may also in part explain the discrepancy.…”
Section: Recent Resultsmentioning
confidence: 99%
“…Cell proliferation is regulated by cell cycle regulators [ 20 ]. Activation and aggregation of CDK and mitogen-dependent signaling pathways regulate adipocyte proliferation and maturation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A list of proliferation genes was selected, such as marker of proliferation Ki-67 (MKI67), PCNA and MCM, which are established cell proliferation markers [34]. Additionally, another set of genes directly associated with cell proliferation, mitotic process and cell division [e.g., myeloblastosis proto-oncogene like 2 (MYBL2), budding uninhibited by benzimidazoles 1 (BUB1), polo-like kinase 1 (PLK1), cyclin-dependent kinase 1 (CDK1) and kinesin family member 11 (KIF11)] were also included [34][35][36]]. Based on our data, more abundant proliferation genes were upregulated in the tECM compared to Col1 groups, such as MKI67, MYBL2, BUB1, PLK1, CDK1 and KIF11 (Fig.…”
Section: Assessment Of Tenogenesis-associated Genes Between the Tecm ...mentioning
confidence: 99%